Targeting of Perforin Inhibitor into the Brain Parenchyma Via a Prodrug Approach Can Decrease Oxidative Stress and Neuroinflammation and Improve Cell Survival - Tampio, Janne (Mol Neurobiol, 2020)
The cytolytic protein perforin has a crucial role in infections and tumor surveillance. Recently, it has also been associated with many brain diseases, such as neurodegenerative diseases and stroke. Therefore, inhibitors of perforin have attracted interest as novel drug candidates. We have previously reported that converting a perforin inhibitor into an L-type amino acid transporter 1 (LAT1)-utilizing prodrug can improve the compound’s brain drug delivery not only across the blood–brain barrier (BBB) but also into the brain parenchymal cells: neurons, astrocytes, and microglia. The present study evaluated whether the increased uptake into mouse primary cortical astrocytes and subsequently improvements in the cellular bioavailability of this brain-targeted perforin inhibitor prodrug could enhance its pharmacological effects, such as inhibition of production of caspase-3/-7, lipid peroxidation products and prostaglandin E(2) (PGE(2)) in the lipopolysaccharide (LPS)-induced neuroinflammation mouse model. It was demonstrated that increased brain and cellular drug delivery could improve the ability of perforin inhibitors to elicit their pharmacological effects in the brain at nano- to picomolar levels. Furthermore, the prodrug displayed multifunctional properties since it also inhibited the activity of several key enzymes related to Alzheimer’s disease (AD), such as the β-site amyloid precursor protein (APP) cleaving enzyme 1 (BACE1), acetylcholinesterase (AChE), and most probably also cyclooxygenases (COX) at micromolar concentrations. Therefore, this prodrug is a potential drug candidate for preventing Aβ-accumulation and ACh-depletion in addition to combatting neuroinflammation, oxidative stress, and neural apoptosis within the brain. [Figure: see text]